2012
DOI: 10.21236/ada564065
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound Studies for Yield Estimation of HE Explosions

Abstract: This report is published in the interest of scientific and technical information exchange, and its publication does not constitute the Government's approval or disapproval of its ideas or findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Station noise levels produce noticeable scatter in period measurements, suggesting this may be a contributing cause to some of the large scatter, particularly for low SNR recordings. This is consistent with the results from Golden et al (2012) who found that the dominant frequency in some cases occurs within a broader plateau making period measurements imprecise. 2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Station noise levels produce noticeable scatter in period measurements, suggesting this may be a contributing cause to some of the large scatter, particularly for low SNR recordings. This is consistent with the results from Golden et al (2012) who found that the dominant frequency in some cases occurs within a broader plateau making period measurements imprecise. 2.…”
Section: Discussionsupporting
confidence: 92%
“…6. Measurement uncertainty and/or broad frequency peaks leading to imprecise dominant period measurements (Golden et al, 2012) The goal of this study is to examine the infrasonic signals produced by a large sample of bolides, which have known properties as reported on the Web by NASA's Jet Propulsion Laboratory (JPL) 1 . These data are based on U.S. government sensor detections of bolides and report bolide characteristics including location, time, energy, height, speed, and entry angle for a subset of events.…”
Section: Introductionmentioning
confidence: 99%
“…These percentiles differ by a factor of two per rocket type, whereas the total amplitude range spans over more than one magnitude order. Such uncertainties are not uncommon for infrasound-based yield/energy relations for explosion-like sources (Golden et al, 2012) because of underlying assumptions concerning propagation and detection conditions and source characteristics. We point out three simplified assumptions leading to Equation 1.…”
Section: Amplitude-energy Relationmentioning
confidence: 99%